Application of Computer Technology in the Design of New Year's Pictures in Beachhead. Issue 2 (May 2021) - Chen, Hong
Abstract: Computer technology, with its unique ability and characteristics, is blending with various industries of the current society. Even in the painting of this traditional need to draw skills of the industry, the computer also by virtue of its powerful processing technology and function and have a place. Tantou New Year pictures are the only handmade woodblock watermark New Year pictures in Hunan Province, which are produced in Longhui Tantou Town, Shaoyang. Longhui Tantou New Year Pictures, formed during Li Shimin's time in the Tang Dynasty, has a history of more than 1, 300 years. With the help of computers brought by The Times [1], the design of beachhead New Year pictures is more conducive to the protection and inheritance of beachhead New Year pictures. In this paper, the advantages of computer technology as a breakthrough point, to explore its application in the design of New Year pictures.